"Adjuvant Radioactive iodine 133 ablation in papillary microcarcinoma of thyroid: Saudi Arabian experience". Issue 1 (December 2015) - AL-Qahtani, Khalid; Al Asiri, Mushabbab; Tunio, Mutahir; Aljohani, Naji; Bayoumi, Yasser; Fatani, Hanadi; AlHadab, Abdulrehman
Abstract Background Papillary Microcarcinoma (PMC) of thyroid is a rare type of differentiated thyroid cancer (DTC), which according to the World Health Organization measures 1.0 cm or less. The gold standard of treatment of PMC is still controversy. Our aim was to contribute in resolving the debate on the therapeutic choices of the surgical and adjuvant I-131 (RAI) treatment in PMC. Methods From 2000 to 2012, 326 patients were found to have PMC and were retrospectively reviewed for clinicopathological characteristics, treatment outcomes and prognostic factors. Results Mean age of cohort was 42.6 years (range: 18–76) and the mean tumor size was 0.61 cm ± 0.24; lymph node involvement was seen in 12.9 % of cases. Median follow up period was 8.05 years (1.62–11.4). Total 23 all site recurrences (7.13 %) were observed; more observed in patients without I-131 ablation (p <0.0001 ). Ten year DFS rates were 89.6 %. Cox regression Model analysis revealed size, histopathologic variants, multifocality, extrathyroidal extension, lymphovascular space invasion, nodal status, and adjuvant RAI ablation the important prognostic factors affecting DFS. Discussion Despite excellent DFS rates, a small proportion of patients with PMC develop recurrences after treatment. Adjuvant RAI therapy improves DFS in PMC patients with aggressive histopathologic variants, multifocality, ETE, LVSI, tumor size (> 0.5 cm) and lymph node involvement. Failure of RAI ablation to decrease risk in N1a/b supports prophylactic central neck dissection during thyroidectomy, however more trials are warranted. Conclusion Adjuvant I-131 ablation following thyroidectomy in PMC patients, particularly with poor prognostic factors improves DFS rates.